Tracheobronchial Stenting for Malignant Airway Disease: Long-Term Outcomes From a Single-Center Study. (November 2013) - Inchingolo, Riccardo; Sabharwal, Tarun; Spiliopoulos, Stavros; Krokidis, Mitiadis; Dourado, Renato; Ahmed, Irfan; King, Juliet; Adam, Andreas
The aim of this retrospective study is to investigate the immediate and long-term outcomes following the insertion of covered and uncovered self-expandable metallic stent (SEMS) for the management of malignant tracheobronchial disease. A total of 49 patients (27 male, mean age 60.9 ± 15 years) underwent 77 SEMS insertions (57 uncovered). The procedure was performed in theater using combined bronchoscopic and fluoroscopic guidance. The study's primary end points included technical success (97.9%), clinical success (91.8%), and symptom recurrence (14.2%). The mean follow-up time was 5.5 ± 5.9 months. We concluded that tracheobronchial SEMSs provide safe and effective minimally invasive long-term management of patients with symptomatic malignant airway disease.